Physical Intimate Partner Violence and Emotional Harm in Five U.S. States - Semenza, Daniel C. (Journal of interpersonal violence, 2024)
The purpose of this study was to assess the relationship between physical intimate partner violence (IPV) victimization and four related aspects of emotional well-being: threat sensitivity, intolerance of uncertainty, impulse control, and access to resources for emotional regulation. We draw on a transactional model of IPV and emotional regulation to theorize how invalidation and partner threats in relationships can generate harmful emotional outcomes. We used representative data collected for residents living in five U.S. states: Colorado, Minnesota, Mississippi, New Jersey, and Texas. Our analytic sample included individuals who reported having been in a romantic relationship in the past year (N = 2,501). Data were collected using a probability-based web panel, between April 29 and May 15, 2022. Following the presentation of descriptive statistics and bivariate correlations, we developed a series of four multivariate models (ordinary least squares [OLS], negative binomial) to analyze the association between IPV victimization and each emotional outcome. All models adjusted for pertinent demographic and geographic control measures. Physical IPV victimization was associated with increased intolerance of uncertainty and heightened threat sensitivity. IPV victimization also corresponded with poorer impulse control and fewer resources for emotional regulation. Overall, our results demonstrate that experiences of physical IPV victimization are linked to poorer emotional outcomes. These outcomes can be harmful to broader mental health and potentially impact long-term well-being. The findings underscore the importance of mental health screenings that extend beyond assessments of diagnostic-level functions and allocating resources toward alleviating other clinically relevant factors that might arise from or even prompt additional exposure to physical IPV.